2018
DOI: 10.1111/pin.12708
|View full text |Cite
|
Sign up to set email alerts
|

Invasive form of ciliated muconodular papillary tumor of the lung: A case report and review of the literature

Abstract: We report a case of a 67-year-old woman with an invasive ciliated muconodular papillary tumor (CMPT) that developed in her right middle lobe. The current tumor was incidentally detected during a follow-up imaging examination for a large cell carcinoma that was resected 10 years previously. Partial removal of the middle lobe showed a 2 cm-sized, solid and myxoid tumor located in the peripheral region. Histologically, this tumor primarily consisted of ciliated columnar cells, mucous cells, and basal cells, all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 20 publications
(133 reference statements)
3
31
0
Order By: Relevance
“…According to the immunohistochemistry results reported in previous studies, in many cases, CK7/CEA/TTF-1 expressions were positive, and most CK20 expressions were negative. These findings are very similar to those for adenocarcinoma ( Sato et al, 2010 ; Chuang et al, 2014 ; Ishikawa et al, 2016 ; Kamata et al, 2016 ; Kon et al, 2016 ; Lau et al, 2016 ; Jin et al, 2017 ; Kim et al, 2017 ; Taguchi et al, 2017 ; Udo et al, 2017 ; Miyai et al, 2018 ) and indicate that CMPTs are potential malignant tumors.…”
Section: Discussionsupporting
confidence: 73%
“…According to the immunohistochemistry results reported in previous studies, in many cases, CK7/CEA/TTF-1 expressions were positive, and most CK20 expressions were negative. These findings are very similar to those for adenocarcinoma ( Sato et al, 2010 ; Chuang et al, 2014 ; Ishikawa et al, 2016 ; Kamata et al, 2016 ; Kon et al, 2016 ; Lau et al, 2016 ; Jin et al, 2017 ; Kim et al, 2017 ; Taguchi et al, 2017 ; Udo et al, 2017 ; Miyai et al, 2018 ) and indicate that CMPTs are potential malignant tumors.…”
Section: Discussionsupporting
confidence: 73%
“…Ishikawa 1 reported the first case in 2002, and named it ciliated muconodular papillary tumor. Literature review indicated a total of 68 cases reported to date 1–10 . The clinicopathological features of the previously reported cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review indicated a total of 68 cases reported to date. [1][2][3][4][5][6][7][8][9][10] The clinicopathological features of the previously reported cases are summarized in Table 1. The tumor size ranged from 2 to 15 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Miyai et al . [6] reported the clinical use of preoperative positron emission tomography–CT scanning without any positive findings. Non-operative biopsy, including bronchoscopy and percutaneous puncture, is also difficult to perform.…”
Section: Discussionmentioning
confidence: 99%